A speed guidance strategy based on cooperative vehicle-infrastructure environment at signalized intersections. Issue 1 (March 2020) - Xu, Liping; Deng, Mingjun
Abstract: It is a problem that most traffic scholars have been studying to enable motor vehicles to pass through signalized intersections without parking or with little parking, so as to improve the traffic efficiency of urban road network and reduce congestion. In the vehicle-road collaboration environment, speed guidance strategy has become an effective solution and trend, aiming at the characteristics and shortcomings of the current trunk signal coordination control as a passive response control based on vehicle arrival drive. In this paper, the principle of speed guidance strategy at signalized intersections is systematically proposed, and the corresponding speed guidance strategy model is proposed according to the different traffic conditions when the guided vehicles arrive at the intersections. This strategy can make the guided vehicles pass through the intersections without stopping or stopping time at least, reduce the delay of vehicles and improve the traffic efficiency at the intersections.